PLEASE HELP ASAP!!! CORRECT ANSWERS ONLY PLEASE!!
Simplify the expression.
![PLEASE HELP ASAP CORRECT ANSWERS ONLY PLEASE Simplify the expression class=](https://us-static.z-dn.net/files/d7a/bc674457d441ea31df22cf22ff0159fe.png)
Answer: A
Step-by-step explanation:
[tex]\dfrac{x^{2}+x-6}{x^{2}-4}*\dfrac{x^{2}-9}{x^{2}+6x+9}[/tex]
[tex]=\dfrac{(x+3)(x-2)}{(x+2)(x-2)}*\dfrac{(x-3)(x+3)}{(x+3)(x+3)}[/tex]
[tex]=\dfrac{(x+3)}{(x+2)}*\dfrac{(x-3)}{(x+3)}[/tex]
[tex]=\dfrac{(x+3)(x-3)}{(x+3)(x+2)}[/tex]
[tex]=\dfrac{(x-3)}{(x+2)}[/tex]